INCREASING THE PRODUCTIVITY OF A FEW VARIETIES OF ONION (ALLIUM ASCALONICUM L.) WITH THE APLICATION OF AMELIORANT - Luta, Devi Andriani; Hanafiah, Diana Sofia; Sabrina, T. (Universitas Negeri Medan, 2017)
AbstractThe Onion (Allium ascalonicum L.) which is cultivated with the ameliorant can expand its conventional functions as a seasoning to different purposes such as medicines and growth regulator. The purpose of this study is to determine the type and dose of ameliorant which are suitable in improving the productivity of a few varieties of onion (Allium ascalonicum L.). This research was conducted in Labuhan Deli District in the province of Sumatera Utara, Socfindo Laboratory and Final Disposal from February – June 2017. The experiment was carried out using a Randomized Block Design with 2 factors and 3 replications. The first factor is varieties consisting of 3 varieties (Bima Brebes, Super Philip, and Medan). the second factor are Ameliorant consisting of 5 dose levels (Control (without ameliorant), Biochar 0,4 kg/m2, biochar 0,8 kg/m2, Urban waste compost 1 kg and Urban waste compost 2 kg/m2). Parameters observed ie plant height (cm), Number of tillers per hill (tillers), and fresh weight production per m2. The results showed that varieties factor gave significantly of difference to the urban waste compost aplication 1 kg can increase the production of super Philip varieties onion with total fresh weight production 1203,57 g.Keywords: Onion, Varieties, Ameliorant